2001
DOI: 10.1038/sj.ejhg.5200694
|View full text |Cite
|
Sign up to set email alerts
|

Multiple lipomas linked to an RB1 gene mutation in a large pedigree with low penetrance retinoblastoma

Abstract: Hereditary predisposition to lipomas is observed in familial multiple lipomatosis (OMIM 151900) and benign cervical lipomatosis (OMIM 151800) and can also be associated with mutations in the MEN1 and PTEN genes (OMIM 131100 and 153480, respectively). In addition, a recent report indicates that a few patients with hereditary retinoblastoma also have lipomas. Here we report on an extended family segregating a splice site mutation in the RB1 gene. Almost all adult carriers of this mutation had multiple lipomas wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 15 publications
2
33
0
Order By: Relevance
“…There were no specific symptoms and, in particular, no muscle weakness.The patient was heterozygous for the RB tumour suppressor gene (the family secreting a splice site mutation in the RB gene: g73 868 A>6). 15 There were no endocrinopathies in other family members.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…There were no specific symptoms and, in particular, no muscle weakness.The patient was heterozygous for the RB tumour suppressor gene (the family secreting a splice site mutation in the RB gene: g73 868 A>6). 15 There were no endocrinopathies in other family members.…”
Section: Case Reportmentioning
confidence: 99%
“…15 The RB gene is the protolyse for a class of recessive human cancer genes in which loss of activity of both normal alleles is thought to be associated with tumorogenesis. 41 The two-step mechanism of RB gene inactivation in RB, proposed by Knudsen,42 has been accorded almost universal acceptance as the general process by which tumour suppressor genes are affected in tumorogenesis.…”
mentioning
confidence: 99%
“…Rieder et al (Rieder et al, 1998) www.intechopen.com Second Malignancies in Retinoblastoma: The Real Problem 25 futher promoted the idea that a predisposing RB1 gene mutation may play a role in the development of lipomas in retinoblastoma patients, by demonstrating the recurrent loss of the same RB1 allele in two different lipomas in the same patient. Others have reported a genetic linkage between a specific RB1 mutation and the development of multiple lipomas, postulating that there is a linked polymorphic allele which acts as a modifying factor by affecting expression of the RB1 gene mutation (Genuardi et al, 2001). These lipomas, when found in hereditary retinoblastoma patients, are preferentially located on the face, neck, shoulders, and upper chest (Genuardi et al, 2001).…”
Section: Benignmentioning
confidence: 99%
“…Others have reported a genetic linkage between a specific RB1 mutation and the development of multiple lipomas, postulating that there is a linked polymorphic allele which acts as a modifying factor by affecting expression of the RB1 gene mutation (Genuardi et al, 2001). These lipomas, when found in hereditary retinoblastoma patients, are preferentially located on the face, neck, shoulders, and upper chest (Genuardi et al, 2001). Li et al (Li et al, 1997) additionally, found twice as many patients with hereditary retinoblastoma and lipomas developed secondary malignancies when compared to those without lipomas.…”
Section: Benignmentioning
confidence: 99%
“…In response to these data, Genuardi et al reported a mutation analysis of a two-generation pedigree with hereditary retinoblastoma and lipomatosis and found that there was no evidence for linkage of a polymorphic focus on chromosome 13q14. The authors hypothesized that an intragenic or extragenic modifying factor was instead responsible for the lipomatosis [50].…”
Section: Benign Second Tumorsmentioning
confidence: 99%